Biaxial Characterization and Mean-field Based Damage Modeling of Sheet Molding Compound Composites - Schemmann, Malte (Schriftenreihe Kontinuumsmechanik im Maschinenbau / Karlsruher Institut für Technologie, Institut für Technische Mechanik - Bereich Kontinuumsmechanik, 2018)
The focus of this work lies on the microstructure-based modeling and characterization of a discontinuous fiber-reinforced thermoset in the form of sheet molding compound (SMC). A microstructure-based parameter identification scheme for SMC with an inhomogeneous fiber orientation distribution is introduced. Different cruciform specimen designs, including two concepts to reinforce the specimens' arms are evaluated. Additionally, a micromechanical mean-field damage model for the SMC is introduced.